Marine heatwaves exceed cardiac thermal limits of adult sparid fish (Diplodus capensis, Smith 1884) - van der Walt, Kerry-Ann (2021)
Climate change not only drives increases in global mean ocean temperatures, but also in the intensity and duration of marine heatwaves (MHWs), with potentially deleterious effects on local fishes. A first step to assess the vulnerability of fishes to MHWs is to quantify their upper thermal thresholds and contrast these limits against current and future ocean temperatures during such heating events. Heart failure is considered a primary mechanism governing the upper thermal limits of fishes and begins to occur at temperatures where heart rate fails to keep pace with thermal dependency of reaction rates. This point is identified by estimating the Arrhenius breakpoint temperature (TAB), which is the temperature where maximum heart rate (fHmax) first deviates from its exponential increase with temperature and the incremental Q10 breakpoint temperature (TQB), which is where the Q10 temperature coefficient (relative change in heart rate for a 10◦C increase in temperature) for fHmax abruptly decreases during acute warming. Here we determined TAB, TQB and the temperature that causes cardiac arrhythmia (TARR) in adults of the marine sparid, Diplodus capensis, using an established technique. Using these thermal indices results, we further estimated adult D. capensis vulnerability to contemporary MHWs and increases in ocean temperatures along the warm-temperate south-east coast of South Africa. For the established technique, we stimulated fHmax with atropine and isoproterenol and used internal heart rate loggers to measure fHmax under conditions of acute warming in the laboratory. We estimated average TAB, TQB, and TARR values of 20.8◦C, 21.0◦C, and 28.3◦C. These findings indicate that the physiology of D. capensis will be progressively compromised when temperatures exceed 21.0◦C up to a thermal end-point of 28.3◦C. Recent MHWs along the warm-temperate south-east coast, furthermore, are already occurring within the TARR threshold (26.6–30.0◦C) for cardiac function in adult D. capensis, suggesting that this species may already be physiologically compromised by MHWs. Predicted increases in mean ocean temperatures of a conservative 2.0◦C, may further result in adult D. capensis experiencing more frequent MHWs as well as a contraction of the northern range limit of this species as mean summer temperatures exceed the average TARR of 28.3◦C.